Morphology, anatomy, palynology and conservation status of Achillea ketenoglui H. Duman - Koyuncu, Onur (Bangladesh Journal of Botany, 2020)
Achillea ketenoglui H. Duman is an endangered species in Turkey. Its morphological, anatomical and palynological features were studied. Microphotographs of the cross sections of stem and root of this species are provided along with the detailed anatomical features and their morphological description with the help of drawings. Distribution and ecology of A. ketenoglui were determined and IUCN risk category was revised. Microphotographs of scanning electron and light microscope was studied, evaluated and discussed for their taxonomic use.